The Effect of Corporate Social Responsibility Disclosure and Capital Structure on Firm Value - Pelangi Putri Bintana; Aulia Fuad Rahman (J-MAS (Jurnal Manajemen dan Sains), 2023)
The primary objective of this empirical investigation is to assess the impact of corporate social responsibility (CSR) and capital structure on the firm value of companies operating in the basic material sector and listed on the Indonesia Stock Exchange during the period of 2018–2021. The study employs descriptive statistics and multiple linear regression analysis as the analytical tools. The purposive sampling method applied in this research resulted in 200 samples. This study finds that CSR and capital structure can increase firm value.